Correlation between Quality-of-Life and the Educational Level of the Population of Maringá/PR - Santos Oliveira, Priscila; Quevedo dos Santos, Natália; Vicentini de Oliveira, Daniel; Garcia, Raiane Caroline; Marques Gomes Bertolini, Sônia Maria (O Mundo da Saúde, 2022)
The level of education can influence the quality of life of a population. Thus, the objective of this study was to verify the correlation between the quality of life (QoL) and the educational level of the population of Maringá, PR. This is a population-based, cross-sectional study with a quantitative approach, carried out with 1237 adults (18 years and over), of both sexes, residing in the municipality. Instruments were applied to obtain data on the sociodemographic profile and the WHOQOL-100 questionnaire. Data analysis was performed using Pearson’s chi-squared test (X2), with a significance of p < 0.05. There was a prevalence of individuals with a good/very good level of QoL in the psychology (62.4%), level of independence (84.9%), social relationships (77.2%), environment (60.6%), and spirituality (83.3%) domains. There was a significant association between the level of education and the domains of independence (p < 0.001), social relationships (p = 0.001), and environment (p = 0.002). It is concluded that there are better QoL indices in the domains of independence, social relationships, and environment in individuals with a higher level of education.